Implementation and Optimization of School Guidance and Counseling Based on the Seven Strategic Approaches of the Indonesian Ministry of Education and the Latest National Regulations - Iskandar, Arief Hakim (International Journal of Applied Counseling and Social Sciences, 2025)
AbstractThis????? article discusses the recent developments in the implementation of Guidance and Counseling services in schools, referring to the latest directions of national education policy. The discussion is focused on the integration of the strategic initiatives of the Seven Great GC Moves launched in 2025 with the provisions in the Minister of Education Regulation No. 11 Year 2025 concerning teachers' working hours fulfillment. After a systematic literature review and an analysis of policy documents, this study reveals several structural and technical issues, such as the still disproportionate ratio of counselors to students, the increased administrative burden, and the still limited institutional understanding of the boundaries and roles of GC professional services.The findings revealed that the comprehensive implementation of the Seven Great GC Moves, which includes individual potential development, emotions management, resilience strengthening, habituation of consistent positive behavior, social relationships strengthening, cross stakeholders collaboration, and creating a learning environment that supports change the orientation of BK services from a curative approach to a model more focused on development and prevention. Moreover, regulatory conformity and cross-sector support have been proven to be key factors in maintaining the continuity and quality of services. Based on the findings, it can be concluded that the success of school Guidance and Counseling services depends heavily on the integration of policy implementation, professional competence development of counselors, and collaborative management in the educational ?????ecosystem. Keywords: Guidance and Counseling; Implementation of Educational Policy; 7 Great Guidance and Counseling Strategies; Teacher Workload; School Counseling Services; Guidance and Counseling Management; Educational Reform